TREATMENT OF SUGAR MANUFACTURING INDUSTRY WASTEWATER BY UPFLOW ANAEROBIC FIXED BED REACTOR AT PRECISE TEMPERATURE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Sugar manufacturing effluent was treated in an anaerobic fixed bed reactor seededwith nongranular anaerobically digested sewage sludge. The ambient room temperatureduring the study period was between 28-37 oC. Successful reactor starts with granulationwas achieved within 90 days of operation. The reactor was started with an OLR of0.031kgCOD/m3/day and was loaded up to the minimum COD 2240 mg/l. Themaximum % COD removal efficiency of 86% for the sugar wastewater at 3.0 daysHydraulic Retention Time with an influent COD concentration of 3960 mg/l wasobtained. The VFA concentration gradually decreased from 54mg/l at 3.00 days HRTand at 24mg/l at 0.6 days HRT. The VFA concentration was decreased drastically withincrease the HRT. The VSS ranges from 98mg/l to 165mg/l at 0.6day to 3.0days HydraulicRetention Time. Under steady state conditions the biomass concentration wasprogressively increased from 98mg/l to 165mg/l to increases the HRT.